Mindful self-compassion for veteran women with a history of military sexual trauma: feasibility, acceptability, potential benefits, and considerations - Tosca D. Braun; Prachi H. Bhuptani; Bailey O’Keefe; Ana M. Abrantes; Eliza Marsh; Cathryn Glanton Holzhauer (European Journal of Psychotraumatology, 2024)
ABSTRACTBackground: Military sexual trauma (MST) is reported by up to 74% of women veterans in the United States and is a driver of poor behavioural and physical health. Self-compassion is a transdiagnostic, protective factor linked with improved posttraumatic stress disorder (PTSD), depression, and health behaviours. Thus, Mindful Self-Compassion training (MSC) may help ameliorate MST-related impacts. However, MSC can also temporarily increase distress (i.e. backdraft). Delivering it with elective trauma-informed yoga (TIY), which regulates acute distress, may help address this issue.Objective: This VA quality improvement project examined feasibility, acceptability, and reported benefits and challenges of a manualized 8-week MSC including within non-randomized subgroups: MSC (n = 4) and MSC+ elective TIY classes (MSC+; n = 4).Methods: Nine women veterans with a history of MST at a Vet Center in the Northeastern U.S.A. enrolled; eight completed, excluding one MSC+ participant. Measures included attrition (n = 9), attendance (n = 8), weekly (n = 8) and posttreatment acceptability (n = 6), validated symptom severity assessments (n = 7), and an exit interview (n = 8).Results: Among completers, MSC attendance was excellent (89%) and higher among in MSC+ vs. MSC (94% vs. 84% sessions completed). On average across the two groups, depressive and PTSD symptom severity decreased by 21% and 30%, respectively. In exit interviews, participants across groups described improved coping with distress and psychiatric symptoms, reduced stress, and improved self-care and health behaviours. Although women in both groups reported backdraft during the programme, MSC+ also reported healthier coping and improved emotional processing.Conclusion: The results of this programme evaluation infer MSC may be feasible, acceptable, and beneficial for women survivors of MST in one Vet Center in the Northeastern USA. Further, temporary elevations in MSC-related distress may be ameliorated with adjunctive TIY. Given requests of women veterans in the USA. for additional complementary and integrative health treatment options, formal research on these approaches is warranted.